The Influence of Work Discipline, Organizational Culture, Quality of Work Life, and Work Motivation on Job Satisfaction (Study of SL Corp Indonesia Employees in the Purwokerto Area) - Yunita, Dwi; Endratno, Hermin; Widhiandono, Hengky; Rahmawati, Ika Yustina (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to determine the influence of work discipline, organizational culture, quality of work life, and work motivation on job satisfaction among SL Corp employees. Using Quantitative Methods with a population of 154 employees and a sample of 111 employees. Questionnaires were distributed in March-May. This research includes descriptive statistics, reliability, and basic assumptions: normality, multicollinearity, and heteroscedasticity. Model feasibility, multiple linear regression test, partial, and coefficient of determination R2 using the SPSS 26 analysis tool. The results of the analysis show that work discipline, organizational culture, and quality of work life have no effect on job satisfaction. Meanwhile, work motivation has a significant positive effect on job satisfaction and has important implications in managing human resources and increasing satisfaction among SL Corp employees.